Intrahepatic fat, irrespective of ethnicity, is associated with reduced endogenous insulin clearance and hepatic insulin resistance in obese youths: A cross‐sectional and longitudinal study from the Yale Pediatric NAFLD cohort. Issue 9 (31st May 2020) - Tricò, Domenico; Galderisi, Alfonso; Mari, Andrea; Polidori, David; Galuppo, Brittany; Pierpont, Bridget; Samuels, Stephanie; Santoro, Nicola; Caprio, Sonia
Abstract: Aim: To evaluate whether intrahepatic fat accumulation contributes to impaired insulin clearance and hepatic insulin resistance across different ethnic groups. Methods: The intrahepatic fat content (HFF%) was quantified by magnetic resonance imaging in a multi‐ethnic cohort of 632 obese youths aged 7‐18 years at baseline and after a 2‐year follow‐up. Insulin secretion rate (ISR), endogenous insulin clearance (EIC) and hepatic insulin resistance index (HIRI) were estimated by modelling glucose, insulin and C‐peptide data during 3‐hour, 9‐point oral glucose tolerance tests. Results: African American youths exhibited the lowest HFF% and a prevalence of non‐alcoholic fatty liver disease (NAFLD) less than half of that shown by Caucasians and Hispanics. Furthermore, African Americans had lower EIC and glucose‐stimulated ISR, despite similar HIRI and plasma insulin levels, compared with Caucasians and Hispanics. EIC and HIRI were markedly reduced in individuals with NAFLD and declined across group‐specific HFF% tertiles in all ethnic groups. Consistently, the HFF% correlated with EIC and HIRI, irrespective of the ethnic background, after adjustment for age, sex, ethnicity, adiposity, waist‐hip ratio, pubertal status and plasma glucose levels. An increased HFF% at follow‐up was associated with decreased EIC and increased HIRI across all groups. Conclusions: Intrahepatic lipid accumulation is associated with reduced insulin clearance and hepatic insulin sensitivity in obese youths, irrespective of their ethnic background.